2021
DOI: 10.3390/su13158232
|View full text |Cite
|
Sign up to set email alerts
|

Transition to a Sustainable Bioeconomy

Abstract: Exceeding planetary boundaries, and especially climate change, requires economies worldwide to decarbonize and to incorporate principles of sustainable development. Transforming a traditional economy into a sustainable bioeconomy by replacing fossil resources through renewable biogenic resources offers a solution to this end. However, seemingly opposing transition perspectives (i.e., technology-based vs. socio-ecological) lead to fragmented efforts, and the exact form of the transition pathway to the goal of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
(106 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the framework is perfectly suited for explaining entrepreneurial activity in the context of the bioeconomy transition. The transition toward a sustainable bioeconomy involves a complex interplay of many factors (Hinderer et al, 2021), with innovation fostered by entrepreneurial activity being a central element (Kuckertz, 2020). However, we argue that the transition itself also serves as an external enabler of entrepreneurial activity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, the framework is perfectly suited for explaining entrepreneurial activity in the context of the bioeconomy transition. The transition toward a sustainable bioeconomy involves a complex interplay of many factors (Hinderer et al, 2021), with innovation fostered by entrepreneurial activity being a central element (Kuckertz, 2020). However, we argue that the transition itself also serves as an external enabler of entrepreneurial activity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Börner et al [22] conceptualize the mechanisms of a bio-based transformation: besides underlying drivers such as population growth, economic growth, climate change, technological innovations and general policies, they point out the main mediators of such a change, which are divided into change mechanisms (policy incentives, markets/trade, and knowledge and innovation transfers) and context factors (natural resource endowment, governance effectiveness, and infrastructure). Hinderer et al [35] found in their expert survey that political strategies, programs and standards are considered as most important for the transition to the bioeconomy, followed by aspects such as competitiveness and investment in research. The supply of biomass, technical progress and consumer awareness were rated as less important by the experts.…”
Section: Factors Influencing the Development Of The Bioeconomymentioning
confidence: 99%
“…<---------------> Different visions translate into various paths to follow for a transition to the envisioned bioeconomy: for example, a technology-based transition based on research and on techno-logical innovations that can be transformed into competitive bio-based products, opposed to a socio-ecological transition that follows sustainability concerns of the biosphere's supply and regeneration capacities. However, there is also a need and possibility to integrate the different perspectives of the transition [24,25]. The bioeconomic transition pathways proposed by Dietz et al [26] are not so much influenced by visions, but take into account the different roles that techno-economic mechanisms can play in the development of the bioeconomy, especially for factor substitutions and for efficiency gains, and differentiate the (1) fossil-fuel substitution, (2) primary sector productivity enhancement, (3) new and more efficient biomass uses, and (4) low-bulk and high value applications pathway.…”
Section: Bioeconomy Typologiesmentioning
confidence: 99%